2018
DOI: 10.1371/journal.pone.0191929
|View full text |Cite
|
Sign up to set email alerts
|

Towards a novel model for studying the nutritional stage dynamics of the Colombian population by age and socioeconomic status

Abstract: Low-and middle-income countries (LMICs) are experiencing a nutritional transition in which the burden of obesity tends to shift towards the lower-socioeconomic status (SES) group. We propose a system dynamics (SD) model for assessing the nutritional stage dynamics of the Colombian urban population by age and SES projected to 2030. This SD model captures the ageing population according to body mass index (BMI) categories and SES. In this model, the transference rates (TRs) between BMI categories by age and SES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 27 publications
1
32
0
1
Order By: Relevance
“…Another large group of models (n = 8) focused on dynamics of population and individual transitions between weight and other health states , all but one using system dynamics modeling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another large group of models (n = 8) focused on dynamics of population and individual transitions between weight and other health states , all but one using system dynamics modeling.…”
Section: Resultsmentioning
confidence: 99%
“…Meisel et al modeled the accumulation and transference of people between the normal weight, overweight, and obesity categories focusing on the urban Colombian population, and tested several interventions for increasing transference to more healthy categories. Frerichs et al focused on the BMI‐category dynamics in US adults and children, while expanding the model to include and explore peer versus adult influence on obesity and testing combinations of prevention and treatment interventions for children and adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many diseases and conditions, such as type 2 diabetes mellitus, coronary heart disease, cancer, hypertension, and musculoskeletal disorders, are associated with obesity [ 46 ]. The included papers investigate obesity among children [ 47 , 48 , 49 , 50 ], women of reproductive age [ 51 ], individuals in low-income urban areas [ 52 ], and lower-socioeconomic status (SES) groups [ 53 , 54 ]. The objectives of the selected papers can be categorized into two main groups: (a) reducing obesity (reactive responses) and (b) presenting interventions for obesity prevention (proactive responses).…”
Section: Discussionmentioning
confidence: 99%
“…Differences in malnutrition prevalence by sex and SES have been also shown in other countries of the region. Results of a novel modelling of nutrition stages dynamics in Colombian population showed that the burden of excess weight is likely higher in those with lower SES (53) . Additionally, Hernandez et al (54) found that food insecure women had a greater percentage of obesity and overweight compared with food secure women, while among men the proportion of obesity and overweight was similar between food secure and food insecure participants.…”
Section: Discussionmentioning
confidence: 99%